O método de Elizabeth Bishop na tradução de poemas brasileiros. - Eduardo Luis Araújo de Oliveira Batista (Cadernos de Tradução, 2005)
This paper analyses Elizabeth Bishop’s translations of Brazilian literature in order to identify her method of translation. It puts together Bishop’s ideas concerning the labor of poetry writing and her opinions about the translations she made and about the process of translation in a general sense. Realizing the literal method as Bishop’s implicit theory of translation, this paper intends to show how this translation method aligns with her ideological thinking and how each one is reflected in the translated texts. Keywords: theory of translation, brazilian literature, Elizabeth Bishop.